2018
DOI: 10.1002/dys.1604
|View full text |Cite
|
Sign up to set email alerts
|

N1 lateralization and dyslexia: An event‐related potential study in children with a familial risk of dyslexia

Abstract: The rapid automatic specialized processing of printed words is signalled by the left‐lateralization of the N1 component in the visual event‐related potential (ERP). In the present study, we have investigated whether differences in N1 lateralization can be observed between Dutch children with and without (a familial risk of) dyslexia around the age of 12 years using a linguistic judgement task. Forty‐five participants were included in the ERP analysis, 18 in the low familial risk group without dyslexia, 15 in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 57 publications
1
16
0
Order By: Relevance
“…No such studies were conducted in pre-literate TD and at-risk of DRD/PR children. In school-aged children, four studies showed similar mean latencies for both TD and DRD/PR groups (Kast et al, 2010 ; Maurer et al, 2011 ; Hasko et al, 2013 ; Zhao et al, 2014 ), whereas one study reported that controls had longer mean latencies than DRD (van Setten et al, 2019 ). In young adults, two studies reported longer mean latencies for DRD than controls (Savill and Thierry, 2011a ; Waldie et al, 2012 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…No such studies were conducted in pre-literate TD and at-risk of DRD/PR children. In school-aged children, four studies showed similar mean latencies for both TD and DRD/PR groups (Kast et al, 2010 ; Maurer et al, 2011 ; Hasko et al, 2013 ; Zhao et al, 2014 ), whereas one study reported that controls had longer mean latencies than DRD (van Setten et al, 2019 ). In young adults, two studies reported longer mean latencies for DRD than controls (Savill and Thierry, 2011a ; Waldie et al, 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-one studies explored the N170w in school-aged children, of which 14 compared TD with DRD/PR. Five studies showed a larger N170w amplitude for DRD/PR as compared to controls (Brem et al, 2013 ; Fraga González et al, 2014 , 2016b ; Zhao et al, 2014 ; van Setten et al, 2019 ), five showed a larger N170w amplitude for controls than DRD/PR (Maurer et al, 2007 , 2011 ; Jucla et al, 2010 ; Kast et al, 2010 ; Bakos et al, 2018 ), and four showed no difference (Araújo et al, 2012 ; Hasko et al, 2013 ; Kemény et al, 2018 ; Pleisch et al, 2019 ). One specific study further divided the TD and DRD children into young ( M age = 8.3) and old ( M age = 11.4) sub-groups and found that in younger groups, TD exhibited a more negative N170w than DRD/PR, whereas the opposite pattern was found for older children (Maurer et al, 2011 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The copyright holder for this preprint this version posted June 21, 2022. ; https://doi.org/10.1101/2022.06.20.496859 doi: bioRxiv preprint instead of leftward lateralization of the word-evoked N1 ERP component (Fraga González et al, 2014Setten et al, 2019). Studies based on fixed-gaze experimental paradigms also revealed enhanced brain activation in the left occipito-temporal region for processing of orthographic information in experienced readers compared to beginners, the dominance of the left hemisphere in orthographic processing was shown to become more prominent with the advancement of reading skills (Brem et al, 2010;Dehaene et al, 2010Dehaene et al, , 2015Pegado et al, 2014).…”
Section: Introductionmentioning
confidence: 99%